Perancangan datawarehouse dan teknologi business intelligence untuk analisa penjualan pada perusahaan retail PT. ABC - I Putu Susila Handika; Putu Praba Santika (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2020)
PT. ABC is one of the retail industries. PT. ABC already has 378 stores spread across Bali, Lombok, and Makassar. Curently PT. ABC has a POS cashier system and warehouse management system to help run its business processes. The problem that often occurs is when the data is more and more, the process of data analysis becomes less optimal because the data is processed very much and to many users who use the system. Thus datawarehouse and business intelligence technology are needed to process data and visualize data into information that can be easily analyzed by stakeholders. Datawarehouse modeling method used in this study is the nine steps kimball method, for ETL process tools are used from Pentaho data integration, and the data visualization process is used power business intelligence tools to be able to display data in graphical form so that stakeholders can analyze data quickly and easily. The application of data warehouses and business intelligence technology can be used and produce information that matches the needs obtained in the analysis of functional requirements. This is evidenced by the results of black box testing that has been received by all stakeholders of PT. ABC.